Staghorn renal stones: a review - Vázquez-González, Juan C.; Romero, Juan J. Granados; Montalvo-Hernández, Jorge; Palacios-Rodríguez, Patricia M.; Mendizabal-Velazquez, Alondra; González-Martínez, Itaty C.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Staghorn lithiasis is described as the presence of stones in the urinary tract that create a mold of the renal collecting system, with the characteristic of being branched. It has a strong association with urinary tract infections caused by urea-splitting organisms. The composition of the stone usually consists of pure magnesium ammonium phosphate (struvite), or a mixture of struvite and calcium carbonate apatite. It is classified as complete and partial. In the complete one, the stones occupy the renal pelvis and the calyceal system, or more than 80% of the collecting system; unlike the partial ones that occupy the renal pelvis and at least two calyces. Computed tomography without intravenous contrast is the imaging method of choice for diagnosis and planning of surgical intervention. Allowing an accurate assessment of the morphology and location of the stones; that will set the standard for guiding percutaneous access. Complete stone cleaning is the cornerstone of staghorn lithiasis treatment. The guidelines of the European Association of Urology and the American Association of Urology mention that percutaneous nephrolithotomy continues to be the treatment of choice for large stones. Conservative management is related to renal loss and urosepsis, reporting a mortality of 28 % up to 30% within 10 years, as well as a 36% risk of developing chronic kidney disease.